Modelling and Analysis of a Solid Waste Composter for Urban Houses. Issue 1 (November 2021) - Srinivasan, Naveen Raj; Chamala Vaishnavi, J; Anuja, V; Akash Menon, S; Devendrán,; Krishnasamy, Karunamurthy; Kumar, Rajendra; Jebaseelan, Davidson
Abstract: Disposal of waste is an important issue faced by sanitation agencies, especially in India, where the volume of waste generated has been increasing rapidly over the last few years. According to the Ministry of Housing and Urban Affairs, as of January 2020, 147, 613 metric tonnes (MT) of solid waste is generated per day in the country. Part of the waste that is expunged on a daily basis from homes, is food and other kitchen waste, which are biodegradable or compostable. In rural areas, such waste is disposed of in landfills, such that they get decomposed to form compost that is used as manure for crops. But this is not feasible in large cities where empty land, as well as the time required for waste to get converted into compost, is in short supply. Composting is a proven method to reduce the volume of waste, to almost 15-20% of its original amount. Therefore, this work is focused on designing an electric composter that could decompose waste artificially, and is compact, efficient, odourless, and easy to operate. This product can thus manage biodegradable waste at the source of its generation, and effectively supplant the wastebasket in a kitchen by occupying no greater space than the latter. The yield of compost would also provide nutritive natural fertilizer to homes wherein kitchen gardens or terrace farms have been set up, as well as promote the creation of the same wherever space is available. In this paper, the important parameters involved in the design of composter, including geometry parameters and the ones of operational significance such as speed and number of blades of agitator and bin temperature, have been discussed thoroughly, along with providing an understanding of the processes and considerations necessitated.